2016
DOI: 10.1007/s11948-016-9829-3
|View full text |Cite
|
Sign up to set email alerts
|

What Do Ethical Guidelines for Epidemiology Say About an Ethics Review? A Qualitative Systematic Review

Abstract: Epidemiological research is subject to an ethics review. The aim of this qualitative review is to compare existing ethical guidelines in English for epidemiological research and public health practice in regard to the scope and matter of an ethics review. Authors systematically searched PubMed, Google Scholar and Google Search for ethical guidelines. Qualitative analysis (constant comparative method) was applied to categorize important aspects of the an ethics review process. Eight ethical guidelines in Englis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Indeed, a recent review of ethical guidelines for epidemiology has shown that not all epidemiological or public health studies require an ethics review. 41 As a general rule, all studies involving primary data collection from human participants need to be reviewed ethically and scientifically by a competent and independent research ethics committees (REC) prior to the start of data collection. 42 43 Studies which perform secondary analysis of existing data may also require ethical review if the analyses fall outside the scope of the informed consent provided (or if no informed consent was provided).…”
Section: When Conducting Multidisciplinary Research Describe the Purmentioning
confidence: 99%
“…Indeed, a recent review of ethical guidelines for epidemiology has shown that not all epidemiological or public health studies require an ethics review. 41 As a general rule, all studies involving primary data collection from human participants need to be reviewed ethically and scientifically by a competent and independent research ethics committees (REC) prior to the start of data collection. 42 43 Studies which perform secondary analysis of existing data may also require ethical review if the analyses fall outside the scope of the informed consent provided (or if no informed consent was provided).…”
Section: When Conducting Multidisciplinary Research Describe the Purmentioning
confidence: 99%
“…The medical examinations within this study were mandatory for all newly arrived refugees, aiming to exclude infectious diseases. Therefore, these examinations were part of the routine public health surveillance and no ethics review was necessary [34].…”
Section: Ethics Approval and Consent To Participatementioning
confidence: 99%
“…Marko Curkovic in his letter ( 2017 ) points out that using Google Search in our systematic review (Piasecki et al 2017 ) could have led to the so-called “bubble effect”, a form of selection bias. We take seriously this concern.…”
mentioning
confidence: 99%